Evaluating Performance and Sustainability of the Waste Bank in Some Cities in East Java Indonesia - Burhanuddin, Achmad Dadang; Yanuwiadi, Bagyo; Arisoesilaningsih, Endang (Jurnal Pembangunan dan Alam Lestari, 2024)
East Java was one of the top five waste Indonesian producers in 2020, and the waste bank is a promising strategy for managing domestic waste better. This study aims to evaluate the performance and sustainability of waste banks in East Java. The research was conducted by observing 40 Surabaya, Malang, and Gresik waste banks. The interview involved managers and 10% of waste bank customers. The bank’s performance and sustainability were determined by some indices: effectiveness, elasticity, zero-waste index (ZWI), and diversion rate. Results showed that waste banks varied in the establishment age (6 to 10 years) and performance (moderate to high). The highest proportion of waste managed by waste banks was plastic and paper. However, some of them also managed degradable waste. The Gresik and Malang District waste banks were established younger and performed better than the Surabaya City ones.  All waste banks reduced waste slightly, as shown by the ZWI index (0.20 to 0.40) and diversion rate (21 to 40%) in reducing waste volume disposal to landfills. Its sustainability constraints were facilities, prices, partners, community or government support, and the COVID-19 pandemic. Waste banks provided some benefits, including increasing sorted waste, environmental sanitation, income, and culture changes. Keywords: Covid-19, East Java, performance, sustainability, waste banks